A decision model for warranted second-hand products considering upgrade level, past age, preventive maintenance and sales volume. Issue 4 (8th October 2018) - Darghouth, Mohamed N.; Chelbi, Anis
Abstract : Purpose: The purpose of this paper is to present a decision model for second-hand products to determine the optimal upgrade level, warranty period and preventive maintenance (PM) effort level which maximize the total expected profit generated by the dealer considering any given past age of the product and the effect of the sales volume. Design/methodology/approach: A mathematical model is developed to derive the optimal triplet: upgrade level, warranty period and PM effort level, which maximize the total expected profit generated by the dealer for any second-hand product with a given past age. Numerical experimentations have been conducted to investigate the effectiveness of the proposed model and to explore the interactions among the model variables. Findings: Numerical experimentations including a sensitivity analysis have been conducted on the model key parameters. The obtained results show that performing PM actions during the warranty period helps the dealers to provide extended warranty for older second-hand products without spending a significant effort on upgrade actions and therefore increase the volume of sales. Also, the interaction between the PM level and the profit margin threshold is demonstrated. Finally, the effect of the sales volume function parameters (the price and warranty elasticity parameters) on the optimal solution is characterized. Research limitations/implications: Given the complexity of the profit function to be maximized involving a considerable number of decision variables with different nature, the authors limited the study to the case where the past age of the second-hand product is known. Practical implications: The proposed model aims to provide second-hand product dealers with a modeling framework that enables them to have a realistic estimation of the generated profit by integrating the marketing and engineering key parameters of the second-hand product. Originality/value: Most of the existing literature dealing with the reliability improvement of second-hand products does not take into account the fact that a realistic estimation of the total profit generated by the dealer requires the consideration of the sales volume. The latter is closely related to the marketing parameters characterized by the warranty period length and the second-hand product selling price. The proposed model introduces the effect of the total sales volume on the total expected profit. The authors also introduce the concept of discrete upgrade levels for a better control of the restoration degree. The authors study the impact of warranty and price elasticity parameters on the optimal solution and the resultant interaction with the customer purchase decision and consequently the sales volume.